Studi Perbaikan Perkerasan Lapis Jalan Tambang dengan Nilai CBR dan DCP - Aldicho Alfiandy Suhendik; Revia Oktaviani; Tommy Trides (Jurnal Riset Teknik Pertambangan, 2022)
Abstract. One of the supporting of a company's production achievement target is to have good mine road access. To be able to hold the load on it like a conveyance it is necessary to calculate the bearing capacity of the soil parameter. Based on the facts of soil inability to produce overburden due to mine access roads experiencing failure. Determination of the design thickness of the structure road layer referred to the California Bearing Ratio (CBR) value and data obtained from Dynamic Cone Penetrometer (DCP). The largest means of transportation used was the Komatsu HD 785 with a load weight of 166,000kg. Based on the DCP test value, the field CBR obtained at the research site ranged from 9.40%- 28.97%.The value of the carrying capacity of the ground was able to support the wheel load of HD 785 with a CBR value of 36%.Retrieved repair the thickness of the pavement above the subgrade suitable for bearing this load was 16inches.The results of the DCP subgrade test with average value of 19.23% and the results obtained for the surface coarse layer using CLY MIX 20% material with a thickness of 9 inch and base coarse layer using CLY MIX 30% material with a thickness of 7 inches. Abstrak. Salah satu pendukung tercapainya target produksi suatu perusahaan dengan memiliki akses jalan tambang yang memiliki kualitas baik. Agar mampu menahan beban diatasnya seperti alat angkut maka diperlukan perhitungan parameter daya dukung tanah. Berdasarkan fakta dilapangan adanya ketidaktercapian terhadap produksi overburden dikarenakan jalan akses tambang mengalami kerusakan. Penentuan rancangan ketebalan struktur lapis jalan mengacu pada nilai California Bearing Ratio (CBR) dan pengambilan data Dynamic Cone Penetrometer (DCP). Adapun alat angkut terbesar yang digunakan berupa Komatsu HD 785 dengan berat bermuatan 166,000 kg. Berdasarkan nilai uji DCP, CBR lapangan yang diperoleh di pada lokasi penelitian berkisar 9,40% - 28,97%. Adapun nilai daya dukung tanah yang mampu untuk menopang beban roda HD 785 yaitu dengan nilai CBR 36%. Diperoleh perbaikan tebal perkerasan di atas subgrade yang sesuai untuk menahan beban ini adalah setebal 16 inch. Hasil uji DCP subgrade dengan nilai rata rata 19,23 % dan diperoleh hasil untuk lapisan surface coarse menggunakan material CLY MIX 20% dengan tebal 9 inchi dan lapisan base coarse menggunakan material CLY MIX 30% dengan tebal 7 inchi.